IMPLEMENTASI PROGRAM GERDU TASKIN TERHADAP PEMBERDAYAAN LEMBAGA KEUANGAN MIKRO DI JAWA TIMUR (Studi Kasus Kabupaten Bojonegoro dan Tuban) - Herry Yulistiyono (MediaTrend, 2015)
Gerdu-Taskin program in East Java is more geared to the pattern of development and program management more integrated and sustainable. The government's efforts through the Dinas Koperasi dan UMKM in East Java province in the empowerment of the poor began in 2002 until 2009.. In 2010 and 2011 the program continued with the name Movement Welfare Society Program (Gema Sejahtera). The activities carried out by providing funds for lending and borrowing taskin group incorporated in microfinance institutions (MFIs). Role of Microfinance Institutions (MFIs) in supporting SME activities interesting to study because the development of MFIs turned out in line with the development of SMEs.The purpose of this study is the evaluation of the performance of the Empowerment Program Gerdu Taskin is intended MFI to obtain information on the results of the impact of the poverty reduction program through the development of enterprises with the capital loan. Grants received by MFIs in Tuban has been used by the Micro, Small and guided them, in which 40% said their business progress after receiving funds Gerdu taskin of East Java province, while in Bojonegoro only 31.67% said no progress. This is quite reasonable given the characteristics and socio-economic circumstances in each different region. The main obstacle in the development aid Gerdu Taskin / Gema  Sejahtera is a matter of human resources, venture capital is given, and the public perception of the program funding Gerdu Taskin / Gema  Sejahtera.To develop MFIs in supporting the SME target is to improve the effectiveness of aid delivery program Gerdu Taskin/ Gema Sejahtera and prevent congestion at the level of beneficiaries of the revolving fund of funds. Another thing that must continue to be encouraged that increase the independence of the MFI beneficiaries through guidance and counseling as well as the development and enhancement of partnerships in business activities MFI beneficiaries in an effort to add value-added production.